Nota sobre Bursera cinerea Engl. (Burseraceae) en el estado de Veracruz - Rzedowski, Jerzy; Calderon de Rzedowski, Graciela (Instituto de Ecología, A.C., 1996)
Bursera cinerea, a species described more than 120 years ago, was neglected by botanists of the present century. Recent explorations performed in the central part of the Mexican state of Veracruz indicate that this tree should have played a major role in the tropical deciduous forest that formerly covered a wide area in this part of Mexico, and still persists in remanents of this forest. B. cinerea closely resembles B. simaruba (L.) Sarg., but differs in its leaves with fewer leaflets and smaller fruits.